2017
DOI: 10.15537/smj.2017.4.16349
|View full text |Cite
|
Sign up to set email alerts
|

ABO blood groups and risk of deep venous thromboembolism in Chinese Han population from Chaoshan region in South China

Abstract: Objectives:To demonstrate the prevalence of ABO blood groups with deep venous thromboembolism in Chinese Han population.Methods:A retrospective study was conducted between January 2010 and March 2015 in The First Affiliated Hospital of Shantou University Medical College in Chaoshan District of Guangdong Province in South China. Eighty nine patients with confirmed diagnosis of deep venous thromboembolism were included. Frequency of blood groups was determined.Results:Of 89 patients with deep venous thromboembol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The potential roles of ABO blood groups in DVT have also been addressed. There is a higher risk for DVT in patients with non-O blood groups than in paients with blood group O [3][4][5]. More recently, we found that the patients in the O blood group had lower warfarin dose requirements than those in the A, B and AB blood groups [6].…”
Section: Introductionmentioning
confidence: 70%
“…The potential roles of ABO blood groups in DVT have also been addressed. There is a higher risk for DVT in patients with non-O blood groups than in paients with blood group O [3][4][5]. More recently, we found that the patients in the O blood group had lower warfarin dose requirements than those in the A, B and AB blood groups [6].…”
Section: Introductionmentioning
confidence: 70%
“…Although inconsistently, these links were reported in numerous conditions, including nonalcoholic fatty liver disease, congenital heart disease, deep venous thrombosis, malaria severity, type 2 diabetes, and different cancers. [29][30][31][32][33][34] Regarding brain tumors, non-O blood groups were repeatedly associated with increased risk and poor prognosis. 24,25,27 In the current study, when compared to pediatric O blood group patients, AB group patients had a 2.79fold higher risk of developing primary brain tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Recently the relationships between ABO blood groups and DVT have been demonstrated. Compared with O blood group, there is higher risk of venous thromboembolism in non-O blood groups [12][13][14]. Furthermore, the blood group remarkably affected the anesthetic effects of propofol [17].…”
Section: Discussionmentioning
confidence: 99%